A Multidimensional Approach for Logistics Routing in the Smart Territory - Cavalcante, Everton; Batista, Thais; Oliveira, Marcel; Pereira, Jorge; Ribeiro, Victor; Oliveira, Matthieu (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais Estendidos do XVIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi_estendido.2022.222988, 2022)
This work proposes a multidimensional approach for analyzing the routing problem to determine the best routes considering data related to different domains of a city. The proposed strategy defines (i) a quality function for each considered dimension to evaluate the route quality and (ii) a utility function that simultaneously considers the different dimensions by weighting each of them at the decision maker's choice. The approach was implemented on a georeferenced smart city platform that integrates data from several city domains. As proof of concept, the platform is used to combine routing and public safety data and indicates the best routes according to these criteria.